Ètimologija karpatskoukrainskogo mifonima Čugajster Etymology of the Carpathian Ukrainian Mythonym Čugajster - Maxim Anatol’evich Yuyukin (Studia Mythologica Slavica, 2018)
The author suggests a new etymology for the mythonym Čugaĭster known in the folklore of the Carpathian Ukrainians.